The housing market in the district of Leiria: a hedonic approach - Carreira, Cláudia (2012)
The real estate housing valuation is, even today, highly subjective. The sales comparison approach, which is based on the determination of housing value suported on sales price of similar housing in a particular market area, remains the most widely used method. Given this situation, the hedonic model should be seen as a solution to improve the quality of assessments, as it determines the price of housing according to the observable values of their different atributes. This dissertation aims to develop a hedonic model for the housing market in the district of Leiria reported to 2010, in order to verify the characteristics of a house that most influence its price. It is proposed a hedonic model of house prices according to the characteristics of a housing listed by Angli and Gencay (1996), Goodman and Thibodaeu (1997), Maurer, Pitzer and Sebastian (2004), Morancho (2003), Ozzane and Malpezzi (1985), Pozo (2009), Rodrigues (2008), Selim (2008) and Wen, Jia and Guo (2005). The cubic functional form is used to proceed with the empirical study. The results indicate that the price of a house is strongly influenced by some location variables, neighbourhood variables and structural variables. Some of these variables have a positive effect on the housing price, such as the location of housing in the county of Óbidos and the number of bedrooms of the housing, specifically housing with four or five bedrooms. Other variables have a negative effect on price, such as usage status of a house, namely used housing and the location of housing in the counties of Marinha Grande and Leiria.